Fundamentul social al economiei de piață - Pasti, Vladimir (Calitatea Vieții, 1990)
The paper examines the way in which common thinking engendered the market economy paradigm, as a general representation of the transition of Romanian society from communism to another form of society. Three models are described as components of this paradigm: (a) the model of society-economy relationship (b) the model of economic successfulness (c) the model of a desirable society and economy. The progress of common thought and the evolvement of the market economy paradigm are explained, against a background of deep changes in the features and relationships of the main social groups in society: (a) the class of industrial workers (b) the technocrats (c) the middle class.